A Natural History of Serious illness Communication over Years, Months, and Days: Presenter(s): Mattias Tranberg, Lund University, Sweden. (April 2023) - Jacobsen, Juliet; Fürst, Carl Johan; Engellau, Jacob; Schelin, Maria
Abstract : Background: Communication with patients and families about serious illness impacts quality of life and helps facilitate decision making. In this study we explored the natural history of serious illness communication from the time of diagnosis of serious illness until death. Methods: Adult patients identified on the Swedish death register as having had an end-of-life care or "breaking point" conversation were eligible for inclusion. 300 patients who had died in a palliative care unit, an oncology unit, or a general medicine unit were randomly selected for manual chart review. Serious illness communication was defined as a documented conversation that referenced prognosis, goals of care, palliative care, or end-of-life care. We included conversations between the patient and clinician, as well as conversations between the clinician and family members. We report on the frequency of conversations in three-time windows, 0-14 days prior to death ("Days"), 14 days – 6 months prior to death ("Months"), and 6 month or longer prior to death ("Years"). Findings: 249 patients had at least one conversation documented in the medical records, 48 of these patients had conversations documented only between physician and next of kin. Patients had an average of 2.1 conversations (range 0-6). 30 patients had their first conversations more than 6 months to several years prior to death, 114 patients had first conversations from 0.5 month-6 months prior to death and 57 patients had a first conversation within 14 days of death. An earlier first conversation predicted an earlier last conversation. Discussion: Measuring the quality of serious illness communication using a days, months, and years framework may help ensure that patients and families have sufficient information for medical and personal decision making. Initiating communication early, more than 6 months before death, may give patients and families more time to prepare for the very end of life.